Standardized Polyalthia longifolia leaf extract induces the apoptotic HeLa cells death via microRNA regulation: identification, validation, and therapeutic potential - Vijayarathna, Soundararajan; Oon, Chern Ein; Al-Zahrani, Majid; Abualreesh, Muyassar H.; Chen, Yeng; Kanwar, Jagat R.; Sahreen, Sumaira; Ghazanfar, Shakira; Adnan, Mohd; Sasidharan, Sreenivasan (Frontiers in Pharmacology, 2023)
Polyalthia longifolia var. angustifolia Thw. (Annonaceae), is a famous traditional medicinal plant in Asia. Ample data specifies that the medicinal plant P. longifolia has anticancer activity; however, the detailed mechanisms of action still need to be well studied. Recent studies have revealed the cytotoxicity potential of P. longifolia leaf against HeLa cells. Therefore, the current study was conducted to examine the regulation of miRNAs in HeLa cancer cells treated with the standardized P. longifolia methanolic leaf extract (PLME). The regulation of miRNAs in HeLa cancer cells treated with the standardized PLME extract was studied through IIlumina, Hi-Seq. 2000 platform of Next Generation Sequencing (NGS) and various in silico bioinformatics tools.The PLME treatment regulated a subset of miRNAs in HeLa cells. Interestingly, the PLME treatment against HeLa cancer cells identified 10 upregulated and 43 downregulated (P<0.05) miRNAs associated with apoptosis induction. Gene ontology (GO) term analysis indicated that PLME induces cell death in HeLa cells by inducing the pro-apoptotic genes. Moreover, the downregulated oncomiRs modulated by PLME treatment in HeLa cells were identified, targeting apoptosis-related genes through gene ontology and pathway analysis. The LC-ESI-MS/MS analysis identified the presence of Vidarabine and Anandamide compounds that were previously reported to exhibit anticancer activity. The findings of this study obviously linked the cell cytotoxicity effect of PLME treatment against the HeLa cells with regulating various miRNAs expression related to apoptosis induction in the HeLa cells. PLME treatment induced apoptotic HeLa cell death mechanism by regulating multiple miRNAs. The identified miRNAs regulated by PLME may provide further insight into the mechanisms that play a critical role in cervical cancer, as well as novel ideas regarding gene therapeutic strategies.